A Study on Occupational Stress of The Women Teachers Belonging To Joint And Nuclear Family - Sharma, Neeta; Student, Km. Anu, m.ed. (International Research Journal of Management, IT & Social Sciences, 2014)
Work is a central part of human life. It is the expression of the basic need to accomplish, to create, to feel satisfaction, and to feel meaningful. The rapidly changing nature of work has resulted in new and far-reaching mechanisms for management control in the form of monitoring, layoffs, and change in work rules, all of which contribute to increased levels of occupational stress. Although office work has always been stressful, several scientific studies and surveys have helped focus attention on the issue of job stress. Among the major negative effects of job stress are its impact on a personâs self-image and self-esteem, which in turn, affects oneâs relationship with family, friends, and co-workers. The problems last far longer than the time we spend at work and are not easily left behind at the end of the day.